Substrate-guided optimization of the syringolins yields potent proteasome inhibitors with activity against leukemia cell lines. Issue 18 (15th September 2015) - Totaro, Kyle A.; Barthelme, Dominik; Simpson, Peter T.; Sauer, Robert T.; Sello, Jason K.
Graphical abstract: Abstract: Natural products that inhibit the proteasome have been fruitful starting points for the development of drug candidates. Those of the syringolin family have been underexploited in this context. Using the published model for substrate mimicry by the syringolins and knowledge about the substrate preferences of the proteolytic subunits of the human proteasome, we have designed, synthesized, and evaluated syringolin analogs. As some of our analogs inhibit the activity of the proteasome with second-order rate constants 5-fold greater than that of the methyl ester of syringolin B, we conclude that the substrate mimicry model for the syringolins is valid. The improvements in in vitro potency and the activities of particular analogs against leukemia cell lines are strong bases for further development of the syringolins as anti-cancer drugs.